Economic valuation of the hydrological environmental services in El Salto, Pueblo Nuevo, Durango - Silva-Flores, Ramón; Pérez-Verdín, Gustavo; Návar-Cháidez, José de Jesús (Instituto de Ecología, A.C., 2016)
This research explored willingness to pay (WTP) and willingness to accept (WTA) payment for conserving water supplies in El Salto, Pueblo Nuevo, Durango. Personal interviews were applied to both El Salto water users to estimate WTP and land resource owners to estimate WTA. Production costs were estimated at the watershed “La Rosilla” near El Salto. The production costs included storage, protection, restoration and water supply to El Salto residents. In addition, production of water was estimated using a mass balance approach. The results showed that the watershed produces on the average 2,10 Mm3/year. About 90% of the water users surveyed in the study were willing to pay for the environmental hydrological service an average of $17,18 for month. Likewise, resource owners were willing to accept about $320,00 for month ($5,26/ha/year) as a compensation to forgo forest harvest and stimulate water production. Differences between WTP and WTA coincide with many other studies that indicate WTA is larger than WTP. Average production cost was estimated at $2,49/m3 of water for the first year and $2,09/m3 for the remaining years over a 10-year planning period. The cumulative WTP, based on the number of households of El Salto, would not be enough to pay for all production costs. Other external programs such as carbon sequestration and government subsidies, etc., are necessary to reduce the gap between estimated WTP and production costs.